Prevelance of Helicobacter pylori in dyspeptic patients - Mustafa GÜLŞEN; Sait BAĞCI; Can UYGURER; Necmettin KARAEREN; Celalettin ÇETİN and Savaş KARAOVA and Mehmet KARALAR and Sadi SOYSAL and Kemal DAĞALP and Ahmet ALPER (Turkish Journal of Gastroenterology, 2019)
-